Giant Anomalous Hall Conductivity in the Itinerant Ferromagnet LaCrSb3 and the Effect of f‐Electrons. Issue 6 (3rd May 2021) - Kumar, Nitesh; Lamba, Neetu; Gayles, Jacob; Le, Congcong; Vir, Praveen; Guin, Satya N.; Sun, Yan; Felser, Claudia; Shekhar, Chandra
Abstract: Itinerant ferromagnets constitute an important class of materials wherein spin polarization can affect the electric transport properties in nontrivial ways. One such phenomenon is anomalous Hall effect which depends on the details of the band structure such as the amount of band crossings in the valence band of the ferromagnet. Here, extraordinary anomalous Hall effect is found in an itinerant ferromagnetic metal LaCrSb3 . The rather 2D nature of the magnetic subunit imparts large anisotropic anomalous Hall conductivity of 1250 Ω −1 cm −1 at 2 K. The investigations suggest that a strong Berry curvature by abundant momentum‐space crossings and narrow energy‐gap openings are the primary sources of the anomalous Hall conductivity. An important observation is the existence of quasi‐dispersionless bands in LaCrSb3 which is now known to increase the anomalous Hall conductivity. After introducing f‐electrons, anomalous Hall conductivity experiences more than twofold increase and reaches 2900 Ω −1 cm −1 in NdCrSb3 . Abstract : Search for high anomalous Hall conductivity in a ferromagnet is important to achieve dissipationless electronics. Itinerant ferromagnet LaCrSb3 exhibits giant anomalous Hall conductivity which is also very anisotropic owing to the quasi‐layered crystal structure. On incorporating f‐electrons, the effect further increases, especially in NdCrSb3 .